REMOVAL OF HEAVY METALS FROM WASTEWATER BY USING PHYTOREMEDIATION TECHNOLOGY - Balamoorthy, Dhivya; Velusamy, Prabu; Rath, Badrinarayan; T R, Praveenkumar; Kabeto, Julla (Journal of Civil Engineering, Science and Technology, 2022)
Contamination of soil and water by toxic metals is a major environmental hazard. The removal of heavy metals from wastewater by chemical methods is very costly and does not apply to the pretreatment process. Hence, phytoremediation process is one of the simplest methods to restore polluted environments. The present research paper investigates the potential of Mimosa Pudica for bio removal of heavy metals like Cd, Pb and Cu from wastewater by using phytoremediation or bioremediation technology. Heavy Metals were detected before and after the process using Atomic Adsorption Spectrometer (AAS). The synthetic wastewater contains Cd, Pb, and Cu at an initial concentration of 0.25mg/l, 0.5mg/l, and 2mg/l was introduced to the soil mass planted by Mimosa Pudica and treated for 16 days through their root. Collected samples were taken for laboratory analysis. The result showed that there was a reduction in Cd, Pb and Cu at a concentration of 0.02mg/l, 0.21mg/l, and 0.4mg/l level of heavy metals from the wastewater. After that, investigation of the potential of Mimosa Pudica accumulates up to 92% of Cd, 58 % of Pb, and 80% of Cu. The evidence presented by this study specified that Mimosa Pudica is an efficient accumulator plant for phytoremediation or bioremediation.